PENGOLAHAN ISYARAT METODE DIFERENSIAL UNTUK LINIERISASI SENSOR KOIL DATAR - Pertiwi, Kisna; Malik, Usman; Umar, Lazuardi (Komunikasi Fisika Indonesia, 2016)
Flat coil sensor works by evaluating changes the mutual inductance of the measuring object immersed in a magnetic field of coil. The spiral coil detects without a physical contact with object made on FR4 Printed Circuit Board (PCB). LC-oscillators are used to evaluate change the inductances of two identical sensors in a differential structure with a measured object of copper beryllium (CuBe) moving parallel between the sensors. Flat coil evaluation sensor using LC oscillator produces the eigen frequency of 1MHz up to 2MHz. The linearization of flat coils are carry out using output differential between two oscillator and shown a linear output.